(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the critical relationship between risk and return in finance and investment. It aims to provide a comprehensive understanding of the concepts of risk and return, their measurement, and their implications for investment decisions. The paper examines various theories, models, and empirical studies to explore the factors affecting risk and return, the role of diversification, risk management techniques, and the trade-off between risk and expected return. By analyzing these key aspects, the paper offers valuable insights for investors and financial professionals in making informed investment choices.